High-dose omega-3 fatty acids have no effect on platelet aggregation or coagulation measured with static and flow-based aggregation instruments and Sonoclot; an observational study in healthy volunteers. (17th November 2018) - Bagge, August; Schött, Ulf; Kander, Thomas
Abstract: The effect of omega-3 fatty acids on platelet aggregation and coagulation is highly unclear. Studies both support and refute the impacts of omega-3 fatty acids on prolonged bleeding time and platelet inhibition as well as its purported positive effects on cardiovascular disease. In a previous pilot study we suggested an inhibition of platelet aggregation measured with multiple electrode aggregometry. Following on that, the aim of the present study was to investigate the effects of supplementary high doses of omega-3 fatty acids on platelet aggregation and coagulation in a sample-size calculated number of healthy volunteers using Sonoclot, multiple electrode aggregometry, and flow-based Cellix instruments after 10 days of omega-3 fatty acid intake. Twelve healthy human volunteers ingested 2520 mg of supplementary omega-3 fatty acids per day for 10 days. Venous blood was sampled and platelet aggregation and coagulation were measured before and after the treatment period. The viscoelastic test instrument Sonoclot, multiple electrode aggregometry, and flow-based Cellix instruments with collagen-coated channels were used to evaluate platelet aggregation and coagulation. There were no differences in any of the measured variables after the treatment period as compared to before. In this well-powered study on healthy volunteers, no effects of high doses of omega-3 fatty acids after 10 days of intake could be demonstrated, either on coagulation or platelet function. Further studies are needed to clarify whether omega-3 fatty acids have a role in the regulation of the putative complex processes in vivo .